The Relationship Between Assetiveness and Self-Esteem Among Students Who Experience People Pleasing Behavior - Ainu Lailla Syawa; Erik Saut H. Hutahaean; Ferdy Muzzamil (Inovan Publisher, 2026)
Assertiveness is an individual’s ability to openly express thoughts, feelings, and needs while continuing to respect others. Meanwhile, self-esteem refers to an individual’s assessment of their own strengths and weaknesses. Based on this, this study aims to examine the relationship between assertiveness and self-esteem among college students who exhibit people-pleasing behavior. This study involved 174 student respondents aged 18–25 years residing in Bekasi City who exhibit people-pleasing behavior. The sampling technique used was purposive sampling, assertiveness was measured using a scale based on the dimensions proposed by Arrindell & Van De Ende, and self-esteem was measured using the State Self-Esteem Scale (SSES) by Heatherton & Poliv. The results of the study indicate a significant relationship between assertiveness and self-esteem, with a significance level of 0.001 (p < 0.05) and a correlation coefficient of -0.198. The negative direction of the relationship suggests that the higher the assertiveness among students exhibiting people-pleasing behavior, the lower their self-esteem. This study indicates that the assertiveness observed is not entirely based on strong self-confidence but is influenced by the need for social acceptance. The implications of this study suggest that the development of assertiveness in students must be accompanied by an increase in self-esteem, so that students are not only able to express themselves but also possess a positive self-assessment in social interactions.